PRINCESS PANTIP PARIBATRA CHUMBHOT AND THE DEVELOPMENT OF CONTEMPORARY ART IN THAILAND, 1960S–1980S - ROHITASUK, SITTHIDHAM (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
This research studies the developments of contemporary art in Thailand through Princess Pantip Paribatra Chumbhot’s patronage of young avant-garde Thai artists from the 1960s to the 1980s. Her establishment of the Suan Pakkard Palace Art Gallery and the Mekpayab Art Centre provided vital platforms for works rejected by the National Art Exhibition and avant-garde artistic expressions beyond the biases and constraints of state-organised exhibitions. The diversity of works presented in these alternative art exhibitions contributed in marked ways to the growth of contemporary expressions in Thai art. She also made significant contributions to the establishment of the Bhirasri Institute of Modern Art, which provided many opportunities for avant-garde artists to exhibit without being affiliated to any educational institution. The Institute allowed artists to explore ideas and to apply the principles of postmodernism, which was popular in the Western world, to art in Thailand